Investigating the Impact of Russian Rise on Russian-American Military Relations during Putin and Obama Era - Atia, Chihani, Nadameriem (جامعة الوادي University of Eloued, 2019)
عبر التاريخ ، كانت العلاقات بين الولايات المتحدة الأمريكية )و م أ( و روسيا تتقلب بين صراع و تنافس و تحالف وشراكة من وقت روسيا القيصرية إلى الاتحاد السوفيتي وتفكك هذا الأخير في أوائل التسعينات. شهدت هذه العلاقات تحولًا جديدًا منذ عام 2000 ، الذي يرتبط بالتغيير في نوعية القيادة على الجانبين الروسي والأمريكي. تحاول هذه الأطروحة التحقيق في تأثير الصعود الروسي على العلاقات العسكرية الروسية الأمريكية خلال فترة بوتين وأوباما. وفقا لذلك ، فإن الدراسة الحالية لها هدفين رئيسيين: أولاً ، تحديد كيف عمل بوتين على صعود الجيش الروسي. ثانياً ، تحليل كيف أثر هذا الصعود على العلاقات العسكرية الأمريكية الروسية في عهد بوتين وأوباما. بالنسبة للنتائج ، كشفت الدراسة أن الصعود الروسي وتحديدا إصلاحات بوتين على الجيش الروسي والعقيدة العسكرية الروسية كان لها تأثيرا كبيرا على العلاقات العسكرية بين البلدين خلال فترة بوتين وأوباما كما تأثرت هذه العلاقات بشكل كبير بالمواجهات في أوكرانيا وسوريا.Throughout history, relations between the United States of America (USA) and Russia have fluctuated between a conflict, a rivalry, a coalition, and a partnership from the time of Tsarist Russia to the Soviet Union (USSR) and the disintegration of the latter in the early 1990s. These relations have witnessed a new transformation since 2000, which is linked to the change in the quality of leadership on both the Russian and American sides. This dissertation attempts to investigate the impact of the Russian rise on the Russian-American military relations during the period of Putin and Obama. Accordingly, the current study has two main goals: first, it determines how Putin rose the Russian military. Secondly, it aims at analyzing how this rise affected US-Russia military relations on the era of Putin and Obama. As for the findings, the study reveals that the Russian rise particularly Putin's reforms on the Russian army and the Russian military doctrine had a great impact on the military relations between the two countries during the period of Putin and Obama. Also these relations were greatly influenced by the confrontations in Ukraine and Syria.
Keywords: العلاقات العسكرية، إصلاحات، روسيا، الصعود الروسي، الاتحاد السوفيتي، الولايات المتحدة الأمريكية (و م أ).; Military Relations, Reforms, Russia, Russian Rise, Soviet Union (USSR), United States of America (USA).